PEMAHAMAN PETUGAS PENGODEAN TERHADAP PELAKSANAAN PENGODEAN DIAGNOSIS PASIEN RAWAT JALAN DI PUSKESMAS PLERET - , CHARIKUL EASTVA L ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Encoding is an important process in the management of medical records. So it must be performed by personnel who have the competence to coding. In the Minister of Health Regulation of the Republic of Indonesia Number 55 of 2013 on the Implementation of Medical Records Jobs mentioned that a medical recorder has the authority to do the clinical classification system and codefication diseases related to health and medical treatment appropriate medical terminology correct. While the standard of competence of doctors, dentists, nurses, dental nurses and midwives not mentioned that they have the competence to do the diagnosis coding. Based on this study it is necessary to look at the coding officers understanding on the implementation of outpatient diagnosis coding. Objective: The purpose of this study was to determine the encoding officer understanding of the implementation of disease diagnosis coding outpatients. Method : This is a descriptive study using a qualitative approach. This study used a phenomenological study design. Subjects of this study were doctors, dentists, nurses, dental nurses and midwives who encodes an outpatient diagnosis of disease. Object of this study is an understanding of the implementation of coding officers outpatient diagnosis coding and medical record file outpatients. Data collection techniques in this study used were interview, observation, test or exams and study documentation. Result : Implementation of disease diagnosis coding outpatient implemented by nurses, dental nurses, doctors, dentists and midwives. There is no policy regarding coding. Average knowledge officers of the ICD-10 coding amounting 33.33%, the percentage of officers understanding the encoding associated with the use of ICD-10 by 16.67% and the officers coding knowledge related to the meaning of punctuation is 43.74%. Average understanding of the medical terminology coding officers was 96.92%. While understanding of the coding officers disease diagnosis coding respondents on the BPU is 33.33%, the BPG is 100% and the KIA is 33.33%. Percentage proper code was 37.5% and the improper code was 62.5%. The improper code then classified based on 4 criteria. Imprecision in accordance with the criteria of A 20%. Imprecision in accordance with the criteria of B is 64%. Which is in accordance with the criteria of C is 1.33%. While Imprecision in accordance with the criteria of D amounting 14.67%.